PENGAWASAN TERHADAP NOTARIS YANG TIDAK TERGABUNG DALAM KEANGGOTAAN ORGANISASI IKATAN NOTARIS INDONESIA (INI) DI KABUPATEN SLEMAN - , Dien Anggraini ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of research, entitled âSupervision of Notary Who Not Incorporated on Organizationâs Membership of Indonesia Notary Society in Sleman Regencyâ is to find out the juridical analysis of perception of Ministry of Justice and Human Rights, Organization of Indonesia Notary Society, and Academicians related to the presence of organizations outside Indonesia Notary Society and supervision of the Notary who not incorporated on organizationâs membership of Indonesia Notary Society in Sleman. This research is an empirical legal research, which examines the primary data in the field or research directly to the public.This research was conducted in Sleman. The research subjects consisted of respondents, they are each of three elements of the Supervisory Council Regional Sleman, Chairman of the Regional Board Indonesia Notary Association in DIY, and Chairman of the BoardIndonesia Notary Association Sleman, and sources consisted of the Chairman of the Honorary Board Sleman. Data collection was conducted by non random sampling by utilizing purposes sampling, which was collected by paying attention to few criteria according to the objects that meets the purposes of the research. All collected data were analyzed with a qualitative method. The results showed that variety of perception given by the parties among others, by Ministry of Justice and Human Rights, Academicians, Committee of Indonesia Notary Society about the existence of organizations outside Indonesia Notary Society is something quite reasonable. Organizations outside Indonesia Notary Society are simply community organizations shaped association. Supervision of notaries who are not incorporated with Indonesia Notary Society in Sleman is the same as supervision which carried out on notaries who are members of Indonesia Notary Society. So, the difference is: if to the notaries who are members of Indonesia Notary Society there are internal supervision through DKD besides external supervision by MPD, whereas the notaries who are not incorporated with Indonesia Notary Society do not have internal supervisor organs as well as Indonesia Notary Society and supervised only by the MPD.